Investigating the evolution of discourse and scientific development during the transition of the governments of the Islamic Republic of Iran - reyhane salehabadi; MohammadReza Hafez Nia (تحقیقات کاربردی علوم جغرافیایی)
Following the victory of the Islamic Revolution, a new perspective on science and technology emerged in Iran. This scientific discourse was profoundly shaped by the principles of the Islamic Revolution and Islamic ideology, leading to the establishment of new values and objectives for the advancement of science and technology. In the post-revolutionary era, as policymakers recognized science and technology as pivotal drivers of societal progress and excellence, they devised scientific policies and strategies aimed at achieving revolutionary and Islamic ideals. This evolving attitude toward science and technology significantly influenced Iran’s scientific and technological development during this period. Given that the Islamic Republic of Iran has assumed a leading role in scientific leadership within the region since 1979, its contributions to the development of scientific capabilities under successive post-revolution governments are noteworthy. To explore this, a descriptive-analytical approach was employed, utilizing reliable data from both domestic and international sources. The research findings indicate that the prevailing discourse in different governmental periods included a focus on industrialization through import substitution and capital resource allocation (1981–1989), modernization and institutional development with an emphasis on advanced technologies (1989–1997), the promotion of advanced technologies, innovation, export expansion, and social justice centered on knowledge-based industries (1997–2005), the transition toward knowledge-based innovation in the economy (2005–2013), and the enhancement of international cooperation with an emphasis on identity and rationality in policy formulation and implementation (2013–2021). The results demonstrate that, in each phase, measures such as the expansion of higher education and scientific research, the establishment of universities and research centers, and the creation of domestic and international scientific networks were implemented in alignment with the dominant discourse.